KOMPILASI HUKUM ISLAM (KHI) SEBAGAI HASIL IJTIHAD ULAMA INDONESIA - Herawati, Andi (Institut Agama Islam Negeri (IAIN) Palu, 2011)
Abstract: Compilation of Islamic law contains the rules of Islamic law in accordance with the conditions of the legal requirements and the legal awareness of Indonesian Muslims. Compilation of Islamic law is a manifestation and result of application of the various sects that exist fiqhi and equipped with Indonesian scholars fatwa in response to problems that arise so that the compilation of Islamic law can be used as a reference in solving the problem of marriage, inheritance and endowments and the compilation of Islamic law also gives legal protection and Indonesian Islamic society inner peace. Kata Kunci: Kompilisai Hukum Islam, ijtihad, ulama Indonesia, fikih, hokum keluarga